2021
DOI: 10.1111/febs.16240
|View full text |Cite
|
Sign up to set email alerts
|

EGFR is a pivotal player of the E2/ERβ – mediated functional properties, aggressiveness, and stemness in triple‐negative breast cancer cells

Abstract: Triple‐negative breast cancer (TNBC) is defined by aggressive behavior, limited response to chemotherapy and lower overall survival rates. The increased metastatic potential of TNBC is a combined result of extensive extracellular matrix (ECM) remodeling that leads to cytoskeleton rearrangement and activation of epithelial‐to‐mesenchymal transition (EMT). The overexpression of epidermal growth factor receptor (EGFR) in TNBC tumors has been linked to induced expression of EMT‐related molecules. EMT activation ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
(73 reference statements)
2
9
0
Order By: Relevance
“…30,31 Additionally, the overexpression of EGFR was also proven in drug-resistant TNBC cells and involved in the high aggressiveness and lethality in patients. 32 Our previous studies also confirmed that EGFR was an effective target for the targeted therapy of TNBC, and several peptide ligands toward EGFR were identified through highthroughput screening of the OBOC library. 33,34 Thus, we hypothesized that screening EGFR-targeting ligands to achieve tumor-targeted therapy might be a promising strategy for the treatment of drug-resistant TNBC.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…30,31 Additionally, the overexpression of EGFR was also proven in drug-resistant TNBC cells and involved in the high aggressiveness and lethality in patients. 32 Our previous studies also confirmed that EGFR was an effective target for the targeted therapy of TNBC, and several peptide ligands toward EGFR were identified through highthroughput screening of the OBOC library. 33,34 Thus, we hypothesized that screening EGFR-targeting ligands to achieve tumor-targeted therapy might be a promising strategy for the treatment of drug-resistant TNBC.…”
Section: Introductionsupporting
confidence: 57%
“…Overexpression of EGFR is frequently associated with tumor metastasis and recurrence . In a previous study, researchers identified an EGFR-targeted peptide with high specificity and affinity through phage display technology, which exhibits great potential in tumor-targeted therapy and diagnosis. , Additionally, the overexpression of EGFR was also proven in drug-resistant TNBC cells and involved in the high aggressiveness and lethality in patients . Our previous studies also confirmed that EGFR was an effective target for the targeted therapy of TNBC, and several peptide ligands toward EGFR were identified through high-throughput screening of the OBOC library. , Thus, we hypothesized that screening EGFR-targeting ligands to achieve tumor-targeted therapy might be a promising strategy for the treatment of drug-resistant TNBC.…”
Section: Introductionsupporting
confidence: 53%
“…In this study, we reported that high ESR2 expression rates have been correlated to decreased overall survival rates in breast cancer patients diagnosed with invasive breast carcinoma. Recent reports indicate that ERb target genes mostly regulate cell survival, movement, and growth (50), and that ERb signaling pathway intersects with EGFR cascade to mediate TNBC cell morphology and stemness (13,15). These data have been corroborated by the strong implication of ERb in EMT process since it acts as EMT promoter by activating the TGFb/Smad3 pathway to promote tumor growth and invasion in metastatic renal cell carcinoma (51).…”
Section: Discussionmentioning
confidence: 91%
“…The discovery of ERb in 1996 as the second nuclear receptor for steroid/thyroid hormones (i.e., 17b-estradiol, E2), after ERa, reserved a new era in the diagnosis, survival estimation and therapeutic targeting of breast cancer (12). While less well established, ERb dynamically communicates with major matrix components, including PGs and epidermal growth factor receptor (EGFR) to stimulate cancer cell behavior, epithelialto-mesenchymal transition (EMT) and stem-like characteristics (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…For example, higher MMPs expression and activity levels guides invasion and metastasis via, among others, promotion of invadopodia formation [ 48 , 50 ]. In addition, SDCs govern angiogenesis and migration by acting as co-receptors of growth factor signals and have recently been recognized as biomarkers of stemness in breast cancer [ 17 , 51 , 52 ]. Finally, CD44 is also implicated as a marker for the induction of cancer stem cell (CSC) phenotype and thus, the therapeutic resistance in various cancers [ 53 , 54 ].…”
Section: Ecm-mediated Cell Signaling and Functional Propertiesmentioning
confidence: 99%